(untitled) (Biological Sciences - PJSIR, 2002)
Perhaps the major impediment to increasing food production in both the humid and dry tropics is that many soils are infer tile (Sanchez 1976; Sale and Mokwunye 1993). One of the fertility constraints in tropical soils is the low level of avail able phosphorus (P) resulting room P deficiency in many soils and from the high capacity of other soils to immobilize P. It is well established that P is one of the major nutrients limiting crop production in the tropics (Naidu et al 1993). At present, the major phosphatic fertilizer used in correcting P deficiency in most tropical soils is single superphosphate (SSP); which is manufactured by acidulating phosphate rock (PR) with sulphuric acid